Distinct immune responses in the early phase to natural SARS‐CoV‐2 infection or vaccination. Issue 12 (6th August 2022) - Peng, Pai; Deng, Haijun; Li, Zhihong; Chen, Yao; Fang, Liang; Hu, Jie; Wu, Kang; Xue, Jianjiang; Wang, Deqiang; Liu, Beizhong; Long, Quanxin; Chen, Juan; et al.
Abstract: Immune responses elicited by viral infection or vaccination play key roles in the viral elimination and the prevention of reinfection, as well as the protection of healthy persons. As one of the most widely used Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) vaccines, there have been increasing concerns about the necessity of additional doses of inactivated vaccines, due to the waning immune response several months after vaccination. To further optimize inactivated SARS‐CoV‐2 vaccines, we compared immune responses to SARS‐CoV‐2 elicited by natural infection and immunization with inactivated vaccines in the early phase. We observed the lower antibody levels against SARS‐CoV‐2 spike (S) and nucleocapsid (N) proteins in the early phase of postvaccination with a slow increase, compared to the acute phase of SARS‐CoV‐2 natural infection. Specifically, IgA antibodies have the most significant differences. Moreover, we further analyzed cytokine expression between these two groups. A wide variety of cytokines presented high expression in the infected individuals, while a few cytokines were elicited by inactivated vaccines. The differences in antibody responses and cytokine levels between natural SARS‐CoV‐2 infection and vaccination with the inactivated vaccines may provide implications for the optimization of inactivated SARS‐CoV‐2 vaccines and the additional application of serological tests.